Effectiveness of a mobile app intervention to prevent dating violence in residential child care - Navarro-Péreza, José J.; Oliver, Amparo; Carbonell, Ángela; Schneider, Barry H. ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
This study focuses on the effectiveness of an app-based, monitored intervention using the Liad@s app in a residential youth-care setting. The aim of this intervention is to reduce maladaptive beliefs and attitudes linked to dating violence: distortions or myths about romantic love and hostile and benevolent dimensions of sexism. A quasi-experimental pre- post study with a control group was carried out. Participants were 71 adolescents from 9 group homes in Valencia (Spain). The outcomes measures were hostile and benevolent sexism (Ambivalent Sexism Inventory - ASI), ambivalence and prejudice towards men (Ambivalence toward Men Inventory - AMI), and myths about romantic love. The results of the intervention were assessed using multivariate analysis of variance (MANOVA). A post-intervention, statistically significant reduction with a medium-large effect size was observed in all dimensions for the treatment group, with eta- square of .25 for the sexism dimensions, .38 for myths, and .21 for ambivalence and prejudices. The experimental group demonstrated significantly more change than the control group on all measures. The benefits of the intervention did not vary by participants sex. These results may be helpful to professionals involved in child and youth care, who can profit from adolescents proclivity toward online communication.
Descripción basada en Psychosocial Intervention, vol. 29, núm. 2 (may 2020), P. 59-66.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Adolescencia; Centros de acogida; Intervención.; Sexismo; Violencia de pareja; Artículos.